Introduction to the Short Film "About My Blood: An Essay on Menopause": by the filmmaker herself - Marambio, Soledad (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
About My Blood: An Essay on Menopause—a link to the film is available at the bottom of the article— explores the silence and the shame that surrounds the biological and culturally loaded stages of perimenopause and menopause.